Utilization Of Organic Waste Bank In Talang Perapat Village Community - Sari, Lora Nopita; Afandra, Rizki; Yanti, Laras Dwi; Ninosari, Devina; Suwarni, Suwarni; Soleh, Ahmad (Universitas Dehasen Bengkulu, 2025)
This study aims to describe the implementation and impact of the Utilization of Organic Waste Banks in the Talang Perapat Village Community, West Seluma District. The method used is descriptive qualitative with data collection techniques through participatory observation, semi-structured interviews, and documentation. The subjects of the study consisted of residents, village officials, and waste bank managers who were selected purposively. The results of the study showed that the utilization of waste banks succeeded in increasing residents' understanding of Organic waste, as well as fostering new habits such as saving waste and utilizing it as organic fertilizer. This behavioral change is supported by the active involvement of village officials who facilitate coordination and ensure the sustainability of the program. This activity is considered very useful because it combines theory and direct practice, making it easier for the community to understand and apply. The utilization of waste banks has proven effective in increasing environmental awareness and encouraging active community participation in maintaining cleanliness in a sustainable manner.